Theory, construction and calculations of agricultural machines - E S Boi (A. A. Balkema, 1991)
The book presents technological and agronomic requirements of operations performed by machines and units. The technical data for these machines are also given. The theory, construction and calculations of machines and implements are discussed in relation to: 1 - soil working; 2 - harvesting cereal crops, root crops and grasses, and 3 - port-harvest treatment of grains. Great attention is paid to the theory of tillage tools and soil cutting with blades suited to different soil-climatic zones